Effects of ambient humidity and sintering temperature on the tribological and antistatic properties of PEEK and CF/PEEK - Pang, Xianjuan; Yue, Shiwei; Huang, Suling; Xie, Jinmeng; Wang, Shuai; Yue, Yun; Song, Chenfei; Li, Dong (Frontiers in Materials, 2023)
Polyether ether ketone (PEEK) is one of the representatives of special engineering plastics. Due to the high molding temperature, the molding method of ordinary plastics and cavity abrasives are difficult to meet the requirements. In view of this, pure PEEK was prepared by vacuum hot pressing sintering technology at different sintering temperatures. The mechanical properties and microstructure characterization results showed that the pure PEEK prepared at 350 ℃ showed excellent friction and wear properties. Then PEEK and CF/PEEK composites were prepared at the optimum sintering temperature. The friction experiments of prepared materials were carried out using UMT-2. The effects of ambient humidity on the tribological properties, wear mechanism and antistatic properties of prepared materials were systematically studied. The surface analysis and properties of the materials were measured by 3D profiler, scanning electron microscope, friction electrostatic tester. The results showed that friction coefficient of PEEK and CF/PEEK composite changed slightly with increase of ambient humidity. The wear rate of PEEK decreased firstly and then increases, which reached the lowest of 3.09×10-5 mm3/Nm when the ambient humidity was 40%. The wear rate of CF/PEEK composite changed slightly, which was significantly lower than that of PEEK, and the main wear mechanism was adhesive wear. The surface friction static electricity of PEEK and CF/PEEK composites decreased with the increase of humidity.